A hope to trust. Educational leadership to support mature students' inclusion in higher education: an experience from Surrey, England. Issue 5 (3rd September 2021) - Farini, Federico; Scollan, Angela Marie
ABSTRACT: This article discusses a Transition Programme to support the inclusion of mature students in Higher Education. The Transition Programme was designed and it is currently provided by a Higher Education institution in Surrey, South-East of England. An outcome of innovative educational leadership, the Transition Programme' successfully solved the paradox of selection for admission to Higher Education programmes, in particular with regard to mature students. The English Higher Education system offers an interesting case for discussion, being caught between the principle of inclusiveness within a 'widening participation' agenda and the contrasting selective principle of 'recruiting with integrity'. The article is motivated by two main aims. The first aim is to contextualize sociologically, within a discussion on the related concepts of hope, trust and risk, the motivations underpinning mature applicants' choice to enter Higher Education. The second aim of the article is to argue for the capability of educational leadership to generate positive change supporting mature applicants' trust in hope for a successful inclusion in Higher Education.